Fourth Year Winner: The Digital Divide in Canada: COMN 4201, Resistance and Subversion on the Internet. CD: Jonathan Obar. - Hatelt, Andrew (Noteworthy: The LA&PS Writing Prizes, 2017)
Andrew Hatelt’s Wikipedia article provides an informative overview of the Digital Divide in Canada. His work shows how inequalities in Canadians’ access to information and communication technologies are associated with geographic and socio-economic factors as well as corporate and government practices and policies, and outlines policy initiatives to address these disparities. Andrew’s research and writing show that what students learn in assignments can be shared with, and is valued by, communities beyond the University. In addition to receiving the Faculty Award, Digital Divide in Canada has been recognized by an internal Wikipedia ‘Did you know?’ Award and is part of Wikiproject Canada.